Predictive epidemiological, clinical and laboratory parameters in the diagnosis of Crimean-Congo hemorrhagic fever - Kaygusuz, Turkkan O.; Tartar, Ayse S.; Balin, Safak O.; Akbulut, Ayhan; Demirdag, Kutbeddin (Future Medicine Ltd, 2023)
Background: The aim of this study is to determine predictive parameters that can be used in the differential diagnosis of Crimean-Congo Hemorrhagic Fever (CCHF) and other diseases with similar clinical and laboratory findings. Materials & methods: In this study, epidemiological, clinical and laboratory parameters of 107 CCHF-positive and 71 CCHF-negative patients were compared. Results: Alanine amino transferase, aspartate aminotransferase, creatine kinase, lactate dehydrogenase, red blood cell, hemoglobin and hematocrit were significantly higher in CCHF-positive patients, whereas total and direct bilirubin, alkaline phosphatase, prothrombin time, international normalization ratio, white blood cell, C-reactive protein and procalcitonin were higher in CCHF-negative patients. In binary logistic regression analysis, an increase in activated partial thromboplastin time level was identified as an independent predictor of having CCHF, while alanine amino transferase, white blood cell and C-reactive protein elevations were identified as independent predictors of not having CCHF. Conclusion: In endemic areas where PCR and serological tests are delayed, knowing the predictive parameters may be of vital importance in the early diagnosis of CCHF.
Keywords: clinic; Crimean-Congo hemorrhagic fever; epidemiological; laboratory; parameters; predictive